2018
DOI: 10.1093/jac/dky097
|View full text |Cite
|
Sign up to set email alerts
|

A survey of practice and opinions on the use of topical antibiotics to prevent surgical site infection: more confusion than consensus

Abstract: There are diverse opinions and practices among healthcare professionals about the use of topical antibiotics for the prevention of SSI. This considerable, and possibly inappropriate, variation in clinical practice needs to be addressed as part of antibiotic stewardship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…There is no consensus among the surgeons or guidelines present regarding topical antibiotics for the prevention of surgical site infection. 11 With time the instruments used in LC have evolved, techniques have improved, and even the port size and the number of ports have reduced, making laparoscopy the gold standard for cholecystectomy. Compared to open cholecystectomy, laparoscopy has the edge of small scars, less pain, quick recovery, early discharge, and early activity.…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus among the surgeons or guidelines present regarding topical antibiotics for the prevention of surgical site infection. 11 With time the instruments used in LC have evolved, techniques have improved, and even the port size and the number of ports have reduced, making laparoscopy the gold standard for cholecystectomy. Compared to open cholecystectomy, laparoscopy has the edge of small scars, less pain, quick recovery, early discharge, and early activity.…”
Section: Discussionmentioning
confidence: 99%
“…116 The routine usage of topical antibiotics for prevention of wound infection has been reported to contribute to the spread of antibiotic resistance. 117 In spite of this knowledge, some clinicians use antibiotics topically to prevent SSI, 118 which also contrasts with the conclusions of a Review of the Clinical Effectiveness and Guidelines: Topical Antibiotics for Infection Prevention published in 2017. 119 Here, two systematic reviews showed that in surgical patients, no statistically significant differences were observed in SSI rates with mupirocin compared with placebo, no intervention or no antibiotic;…”
Section: Surgical Techniquementioning
confidence: 95%
“…Indications for the use of specific types of antimicrobials, application techniques, dosages, elution properties and pharmacokinetics are poorly defined in the clinical setting leading to arbitrary variation in practice which is becoming a significant issue in orthopaedic trauma surgery [77,78].…”
Section: Local Antimicrobial Therapy and Dead Space Managementmentioning
confidence: 99%